EFFECT OF THYME HYDROSOL ON SPONTANEOUS AND ACETYLCHOLINE-INDUCED GASTRIC FUNDUS CONTRACTIONS - Dragićević, Anđela; Stojanović, Nikola; Matejić, Jelena; Pavlović, Dragana (Archives of Pharmacy, 2023)
Hydrosols are obtained during the extraction of essential oils from aromatic plants. Hydrosols contain a certain amount of bioactive molecules, which are quantitatively and qualitatively different from essential oils (1). Thyme essential oil has cytotoxic properties in high concentrations and can damage intestinal cells when administered orally (2); therefore, hydrosol application is a potentially safe way to use the diluted water-soluble fractions of essential oils. The aim of this study was to investigate the effect of different volumes (10-1000 µl) of hydrosol obtained by hydrodistillation of the aerial part of Thymus vulgaris L. (Lamiaceae) on the spontaneous and acetylcholine (Ach)-induced contractions intensity in the isolated rat fundus (3). Application of different volumes of T. vulgaris hydrosol significantly decreased the intensity of spontaneous contraction of the isolated rat fundus in a dose-dependent manner. The application of 250, 500, and 1000 μl of hydrosol induced more than 50% relaxation in fundus tissue (p